Analisis Ekonomi Syariah Terhadap Praktik Kerjasama Bagi Hasil Pada Bisnis Peternakan Ayam Broiler pada Mitra Peternakan Desa Sukomoro Kabupaten Magetan - Nasrudin, Suryana Agus; Albanjari, Fatkhur Rohman; Rezqi Syakarna, Nugraheni Fitroh (Universitas Muhammadiyah Ponorogo, 2024)
This research aims to determine the Sharia economic analysis of the practice of profit sharing cooperation on broiler chicken farms. This research method uses a qualitative approach by conducting in-depth interviews with broiler chicken breeders who have implemented profit sharing cooperation practices. The data obtained was then analyzed. The results of the analysis show that the practice of profit sharing cooperation in the broiler chicken farming business can be in accordance with sharia economic principles. Profit sharing is a mechanism for fair profit sharing between investors and breeders, where investors provide capital and breeders provide labor and farm management. Profit sharing is carried out based on previously agreed percentages, taking into account the risks and contributions of each party. However, there are several challenges in implementing profit sharing cooperation practices in the broiler chicken farming business. One of them is the difficulty in determining the value and fair distribution of results, especially in the face of fluctuations in feed prices and the availability of broiler chickens on the market. Apart from that, an incomplete understanding of sharia economic principles is also an obstacle in implementing this practice.